2012
DOI: 10.1210/jc.2011-2864
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and Gender on Papillary Thyroid Cancer Survival

Abstract: Although the overall outcome of women with PTC is similar to men, subgroup analysis showed that this composite outcome is composed of two periods with different outcomes. The first period is a period with better outcomes for women than men when the diagnosis occurs at younger than 55 yr; the second is a period with similar outcomes for both women and men diagnosed at ages greater than 55 yr. These data raise the question of whether an older age cutoff would improve current staging systems. We hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
122
4
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(144 citation statements)
references
References 50 publications
10
122
4
8
Order By: Relevance
“…Experimental studies have revealed inhibitory effects of the estrogen receptor beta on the development of thyroid cancer (15,16). A recent epidemiologic study has also demonstrated a better prognosis in younger female patients (!55 years), before menopause, and those aged O55 years had similar outcomes to those of male patients, suggesting a sex disparity in thyroid cancer outcomes (10). However, the beneficial effect of hormones in female patients remains unclear (14), and our results are not consistent with the results mentioned above; in our study, improved prognosis in female patients was observed in those !65 years, and in the patients in the post-1999 time period, the differences in the prognostic outcomes between the sexes were no longer observed for any age group (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Experimental studies have revealed inhibitory effects of the estrogen receptor beta on the development of thyroid cancer (15,16). A recent epidemiologic study has also demonstrated a better prognosis in younger female patients (!55 years), before menopause, and those aged O55 years had similar outcomes to those of male patients, suggesting a sex disparity in thyroid cancer outcomes (10). However, the beneficial effect of hormones in female patients remains unclear (14), and our results are not consistent with the results mentioned above; in our study, improved prognosis in female patients was observed in those !65 years, and in the patients in the post-1999 time period, the differences in the prognostic outcomes between the sexes were no longer observed for any age group (data not shown).…”
Section: Discussioncontrasting
confidence: 71%
“…These changes might also be related with temporal changes in the previously well-known prognostic factors. In fact, several recent studies have reported changes in the effect of age and gender on the risk and prognosis of thyroid cancer (10,11). We aimed at investigating the changes in the impact of prognostic factors for thyroid cancer during a long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The data collection and analytical methods of the NTCTCS have been described elsewhere (8,9,(14)(15)(16)(17)(18)(19)(20). Briefly, 11 North American centers contributed patient data, with registration beginning in January 1987 (this data analysis captures patients registered through to 2011).…”
Section: Registry Protocol and Data Collectionmentioning
confidence: 99%
“…In a previous analysis, the authors' group noted that most deaths in thyroid cancer patients appear to occur in those diagnosed after the age of 55 years (9). Other studies have variously suggested under-staging of certain patients younger than 45 years of age (10), or that mortality does not rise before an age at diagnosis of 50 years (11) or 55 years (12).…”
mentioning
confidence: 99%
“…In fact, in another review of this issue, Derwahl & Nicula (2014) explore the role of estrogen in thyroid tumors, demonstrating that, besides being a potent growth factor for both benign and malignant thyroid cells, estrogen exerts its growth-promoting effect via a membrane-bound link to the tyrosine kinase signaling pathways MAPK and PI3K. In addition, the fact that estrogen is involved in the regulation of angiogenesis and metastasis may explain the differences observed in the clinical evolution between genders (Jonklaas et al 2012). It is important to notice that estrogen may also be an important stimulator of stem and progenitor cells (Derwahl & Nicula 2014).…”
mentioning
confidence: 99%